Isolation and Identification of Endophytic Fungi from Leave and Stem of Calopogonium mucunoides - Dian Fitriarni; Rina Sri Kasiamdari (Journal of Tropical Biodiversity and Biotechnology, 2018)
Thirty-seven isolates of endophytic fungi were isolated from leaves and stems of Calopogonium mucunoides collected from PTPN PTPN XII (Persero) Rubber Plantation, Klatakan, Kecamatan Tanggul, Kabupaten Jember, Jawa Timur. All isolates were identified based on morphological characteristics using the light microscope. The 37 isolates of endophytic fungi are members of Deuteromycota and Basidiomycota and classified to genera Phoma, Phomopsis, Corynespora, Rhizoctonia, Helicosporium, Curvularia, Torulomyces, Gliocladium, Gloeosporium, Acremonium, Tripospermum, Aureobasidium, Colletotrichum, Humicola, Fusarium, Sclerotium, and sterile hyphae.